ANALISIS PENGENDALIAN INTERNAL TERHADAP PIUTANG LEASE: STUDI KASUS PADA PERUSAHAAN PEMBIAYAAN PT. FIF - Dian Oktaviani; Ludwina Harahap (RELEVAN : Jurnal Riset Akuntansi, 2022)
Abstract The implementation of internal control system might help the company to achieve its goals effectively, efficiently and compliance. Effective internal controls might also give assurance to shareholders, and stakeholders' that financial statements provide the propriate quality information. Internal control systems might also help detect and prevent the emergence of fraud, especially those committed by company insiders. As a leasing company in Indonesia, PT. FIF has certainly executed an internal control system that help making the company's activities effectively, and efficiently. Account receivables are one of company assets that must be managed and monitored effectively so as to help the company achieving the goal; those are profits and cash flow streams. However, some companies have not realized the importance of internal control. It occurs in PT. FIF, a leasing company in Jakarta. Using the COSO internal control framework, the research with qualitative descriptive methods aims to analyze the implementation The data and information were taken from interviews, observations and documentation. The results show that generally the company has been implemented all five elements of internal control based on the COSO framework. The control environment, risk assessment has been effective with establishing Structure, Responsibility, and Authority, commitment to competence, Standard Operational and Procedure (SOP), etc, especially in the collection division. While, controlling activity has not been done effectively. There is no separation of task clearly, and file or data documentation. Double job or assignments might provide opportunities for errors, fraud, whether it is intentional or not. The other element is information and communication is already done, both top down and bottom up communication channel. While, the last component is that monitoring activities have not been practice well. Management's role in the internal control system is critical to its effectiveness. Managers, auditors, don't have to look at every single piece of information to determine that the controls are functioning and should focus their monitoring activities in high-risk areas. Spot-checking transactions can provide a reasonable level of confidence that the controls are functioning as intended. Keywords: Internal Control, Accounts Receivable, lease, COSO framework